Assessment of amyloid β in pathologically confirmed frontotemporal dementia syndromes. Issue 1 (29th May 2017) - Tan, Rachel H.; Kril, Jillian J.; Yang, Yue; Tom, Nicole; Hodges, John R.; Villemagne, Victor L.; Rowe, Christopher C.; Leyton, Cristian E.; Kwok, John B.J.; Ittner, Lars M.; Halliday, Glenda M.
Abstract: Introduction: The diagnostic utility of in vivo amyloid β (Aβ) imaging to aid in the clinical distinction between frontotemporal dementia (FTD) and Alzheimer's disease remains unclear without data on the prevalence and severity of Aβ in pathologically confirmed FTD syndromes. Methods: Aβ was assessed in 98 autopsy‐confirmed FTD and 36 control cases, and the pathological accuracy of 11 C‐Pittsburgh compound B (PiB)–positron emission tomography imaging was assessed in a subset of FTD cases ( n  = 15). Results: Aβ was identified in a similar proportion of FTD syndromes and age‐matched controls and increases with age. Alzheimer's disease pathology was identified in all cases with high PiB retention and in one case with low PiB retention. We further demonstrate a strong regional correlation between volume fraction of histological Aβ with PiB standard uptake value ratio scaled to the white matter. Discussion: The present study provides a pathologic reference to assist in the interpretation of in vivo assessments in FTD syndromes.